BRICS and International Law: A Critical Comparative Analysis of Sovereignty and Non-Intervention Policy - Rahmawati, Diah Ayu; Haryono, Haryono; Utari, Woro; Hartantien, Sinarianda Kurnia; Soraya, Joice (West Science Interdisciplinary Studies, 2024)
The BRICS group, made up of Brazil, Russia, India, China, and South Africa, has become an influential instrument of international law, especially with respect to its promotion of sovereignty and the policy of non-intervention. The paper discusses both the collective and individual contribution of BRICS countries toward the interpretation and implementation of these principles through a normative juridical perspective. The findings reveal that while BRICS upholds state sovereignty and is against unilateral interventions, huge variations between member states remain because of the diverse historical, cultural, and strategic contexts in which they are situated. Case studies, including Russia's actions in Crimea and China's South China Sea policies, highlight both alignment and contradictions within the bloc. While BRICS contributes to the positive promotion of sovereignty and the espousal of multilateralism in global governance, challenges in terms of incoherent practices and lack of cohesion remain. The present research underlines BRICS' potential to lead a multipolar international legal system in striking a balance between state autonomy and collective responsibility.
Keywords: Sovereignty; Non-Intervention; BRICS; International Law; Multilateralism